Predictive performance of factors associated with malignancy in intraductal papillary mucinous neoplasia of the pancreas. Issue 1 (5th February 2018) - Heckler, M; Brieger, L; Heger, U; Pausch, T; Tjaden, C; Kaiser, J; Tanaka, M; Hackert, T; Michalski, C W
Abstract: Background: Estimation of the risk of malignancy in intraductal papillary mucinous neoplasia (IPMN) of the pancreas is a clinical challenge. Several routinely used clinical factors form the basis of the current consensus guidelines. This study aimed to determine the predictive values of the most commonly assessed risk factors. Methods: A meta-analysis of individual risk factors of malignancy in IPMN was performed. Contingency tables were derived from these data, and sensitivity, specificity, negative and positive predictive values, and diagnostic odds ratios (DOR) were determined. Hierarchical summary receiver operating characteristic (HSROC) curves for each factor were calculated and the respective area under the curve (AUC) was assessed. Results: A total of 3443 studies were screened initially. Analysis of recent literature revealed 60 studies with 13 relevant risk factors including clinical, serological and radiological parameters. The largest area under the HSROC curve was found for weight loss (0·84) and jaundice/raised bilirubin level (0·80), followed by increased carcinoembryonic antigen (CEA) (0·79) or carbohydrate antigen (CA) 19-9 (0·78) levels. The most sensitive factors were patient age (71 per cent) and mural nodules (65 per cent), and jaundice/raised bilirubin level (97 per cent) and increased CEA level (95 per cent) were most specific. None of the analysed factors reached a positive or negative level of prediction beyond 90 per cent. Conclusion: None of the established criteria safely distinguishes malignant from non-malignant lesions. Graphical Abstract: The diagnosis of intraductal papillary mucinous neoplasia (IPMN) is still accompanied by a high grade of uncertainty–for patients and treating physicans. The authors meta-analysed the current literature and found that none of the established diagnostic parameters safely excludes malignancy. No clinically useful system available.